STUDI KOMPARASI CORPORATE SOCIAL DISCLOSURE PADA LEMBAGA KEUANGAN DAN PERBANKAN DI INDONESIA DAN MALAYSIA - Samputri, Murvina Martha (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims at examining the difference of corporate social disclosure level and examining the effect of a company’s characteristics on the corporate social disclosure of the financial service and banking companies in Indonesia and Malaysia. The research samples are financial service and banking companies listed in the Indonesia Stock Exchange (BEI) and Bursa Malaysia. 25 Indonesian companies and 19 Malaysian companies are purposively selected as the samples. The result of independent sample t-test shows that corporate social disclosure of the financial service and banking company in Indonesia and Malaysia is not different. In addition, the multiple-linier regression test indicates that company’s size influenced level of corporate social disclosure, it can be concluded that big size companies in both countries use corporate social disclosure in order to improve the company's reputation. There is a positive influence on the activity ratio to the level of corporate social disclosure on financial service and banking companies in Malaysia, because of the financial service and banking companies in Malaysia with a tendency to perform well in managing their finances then have more resources, which can be used to expand the level of corporate social disclosure to find support of the stakeholders.Keywords: corporate social disclosure, company’s characteristic, company’s size, company’s age, company’s activity, profitability, GRI